REPRESENTASI BUDAYA TIONGHOA DALAM FILM ANIMASI WISH DRAGON ANALISIS SEMIOTIKA JOHN FISKE - Nurdin Fajar; RR Roosita Cindrakasih; Sultan Himawan (An Nafi': Multidisciplinary Science, 2025)
This research aims to identify the representation of Chinese culture in the animated film Wish Dragon using John Fiske’s semiotic approach. The film presents Chinese culture through various cultural symbols, such as character portrayals, settings, traditional clothing, belief systems, and celebrations, all visually depicted. Behind these symbols lies the cultural meaning of Chinese traditions. The analysis was conducted using a qualitative method through John Fiske’s semiotic approach, which consists of three levels of coding: reality, representation, and ideology. Data collection techniques included observation of scenes in the film and source triangulation. The findings show that Wish Dragon represents Chinese culture through symbolic elements that reflect the values, traditions, and cultural identity of Chinese society. The film not only uses culture as a backdrop but also conveys it meaningfully to the audience.